PENGARUH BUDAYA ORGANISASI TERHADAP LOYALITAS KARYAWAN DI SEKTOR PERBANKAN - SETYOWATI, LILIS (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
Abstract. This research examines organizational culture's influence on employee loyalty in Indonesia's banking sector. The approach used in this research is qualitative with a case study method, involving in-depth interviews with 20 employees from several banks operating in Indonesia. Data is also collected through observation and analysis of related documents to provide a more comprehensive context. The research results show that organizational culture significantly impacts employee loyalty. An organizational culture that is open, inclusive, and supports innovation tends to increase loyalty, while a rigid and hierarchical culture can decrease employee commitment. The main factors that influence loyalty include open communication, appreciation, and recognition, as well as management support for employee welfare. This research also reveals that the match between individual values ​​and organizational culture plays an important role in reducing turnover. This research implies that banks need to develop a positive and supportive organizational culture to increase employee loyalty. This can be achieved by improving internal communications, providing fair rewards, and showing concern for employee well-being. In this way, banks can retain quality employees, increase productivity, and achieve long-term success.